Enrichment and characterization of autotrophic Thiobacillus denitrifiers from anaerobic sludge for nitrate removal. (May 2018) - Yang, Yan; Gerrity, Sean; Collins, Gavin; Chen, Tianhu; Li, Ruihua; Xie, Sihuang; Zhan, Xinmin
Graphical abstract: Highlights: Thiobacillus -dominated (55%) denitrifiers were enriched from anaerobic sludge. A simple method using thiosulfate to enrich denitrifiers in 28 days was proposed. Autotrophic denitrification rate of the final enrichment was 21 mg N (g VS d) −1 . No accumulation of nitrite and N2 O in the batch and continuous biofilters. Nanostructured pyrrhotite supports autotrophic denitrification. Abstract: An efficient and cost-effective method was established to enrich sulfur-based autotrophic denitrifiers from anaerobic sludge from a municipal wastewater treatment plant. Successful enrichment was achieved using thiosulfate as a substrate after 28 days at 30 °C under anaerobic conditions. Terminal restriction fragment length polymorphism (TRFLP) and high-throughput Illumina sequencing of 16S rRNA genes were applied to investigate the evolution of the microbial community during the enrichment, and observed a significant reduction in the bacterial diversity along the enrichment. Illumina sequencing showed that Thiobacillus became the dominant genus in the final enrichment culture, in which autotrophic denitrification rate was 21 mg N2 -N (g VS d) −1 . In addition, flow-through nanostructured pyrrhotite (NPyr) packed biofilters seeded with the final enrichment culture were evaluated for the autosulfurotrophic denitrification of nitrate-contaminated water. Stable and complete nitrate reduction of 30.24 mg NO3 − -N kgNPyr −1 d −1 was achieved under a loading rate of 56 mg NO3 − -N (L d) −1 in a 30-day trial. Further research is needed to determine the potential of NPyr-packed biofilters to remove nitrogen, and to verify the efficacy of this technology for simultaneous nitrogen and phosphorus removal in general engineering practice.